HIV Prevalence and Associated Factors in Key Groups and General Population Treated at a Health Care Institution in Colombia in 2019: A Cross-Sectional Study (2020)
ABSTRACT : Background: Research conducted on the prevalence of HIV/AIDS and its associated factors among key groups in Colombia is scarce. The few available studies show heterogeneity in their results and increasing trends of infection. This study analyses the prevalence of HIV and associated factors in key groups served at a health care institution in Colombia in 2019. Methods: We performed a cross-sectional study with the sample comprised of 5771 subjects from the general population, the LGBTI community, sex workers, people who inject drugs and prisoners. The diagnosis was based on a fourth-generation ELISA. Variables related to sociodemographics, healthcare, sexual risk factors and biological measures of infected subjects were analysed. Prevalence and odds ratios were calculated with 95% confidence intervals, and logistic regression models were performed to identify confounding variables and interactions between independent variables using SPSS 25.0. Results: The prevalence of HIV was 0.27% among the general population, 0.53% among sex workers, 0.66% among the homeless, 2.44% among transgender persons, 2.44% among prisoners, 5.36% among men who have sex with men and 7.92% among injection drug users. The explanatory model showed higher prevalence among men, those with higher education levels, those with no health coverage, those who have sex with people from key groups and those with sexually transmitted infections, with some interactions between the latter variables. Conclusion: A high prevalence of infection was found in the key groups, while the main explanatory factors for high infection rates were identified. The data show that national and global goals related to controlling HIV have not been achieved mainly in groups that are at a higher risk of obtaining and transmitting it and, paradoxically, also that are excluded from the national health coverage.